A comparative dataset on the GC–MS analysis and antioxidant activity of Selaginella bryopteris from different geolocations of IndiaMendeley Data - Utkarsha Srivastava; Ashwani Mathur (Data in Brief)
Selaginella bryopteris (L.) Baker, is a lithophytic pteridophyte of the Selaginellaceae family. It has been reported for its medicinal properties due to its rich phytocompound pool. The current work reveals a comprehensive dataset on the phytochemical profile of this species procured from different geolocations in the deccan terrain of India. The extraction was undertaken with four solvents namely, water, ethanol, methanol and acetone. The phytocompound analysis was done using qualitative detection methods. The acetone and methanolic extracts were analysed for their phytochemical composition, using GC–MS (Agilent 5977B EI/CI MSD), on the basis of area (%) covered in the chromatogram up to the retention time (RT) of 23 min. The GC–MS analysis of plant from Tamil Nadu showed the maximum number of peaks in both the acetone and methanolic extracts (83 and 74 respectively). A total of 12 and 14 peaks were observed in the chromatogram of methanolic extracts of plant from Karnataka (SBK) and Maharashtra (SBM), respectively. The acetone extracts of Karnataka and Maharashtra showed 77 and 42 peaks respectively. Some common compounds tentatively identified by GC–MS analysis were Hexadecanoic acid, methyl ester, trans-13-Octadecenoic acid, methyl ester and Eugenol. The comparative antioxidant assessment of the extracts from all three geolocations was undertaken by three different methods of free radical scavenging activity by DPPH assay, FRAP assay and total antioxidant capacity determination by Phosphomolybdate assay. Ethanolic and methanolic extracts showed nearly similar IC50 for all the antioxidant assays. The results were statistically evaluated using Data Analysis tools of Microsoft Excel. Single factor ANOVA (p < 0.05) was used to determine the significance of data. The present results add to the limited data available on the comparative analysis of antioxidant potential and GC–MS phytochemical profile of Selaginella bryopteris.